Becoming Brianna - Libenson, Terri (Libenson, Terri. Emmie & friends., 2020)
Everyone knows how much brainy Bri likes the spotlight (not). So why did she ever agree to something that forces her to learn a new language, give a speech, help organize a party, and juggle drama at school and home?! As the big event inches closer, Bri wonders if it's all worth it. . . .Told in alternating past and present chapters, Bri's heartwarming story unfolds over the eight months leading up to her bat mitzvah--as well as over the course of the big day itself.